Additive biomass models for Larix spp. single-trees sensitive to temperature and precipitation in Eurasia - Usoltsev Vladimir А.; Zukow, Walery; Osmirko, Anna A.; Tsepordey, Ivan S.; Chasovskikh, Viktor P. (Ecological Questions, 2019)
The analysis of the biomass of larch (genus Larix spp.) trees on the total component composition based on regression equations having the additive biomass structure. Two trends of changes in the tree biomass structure are revealed: due to the mean January temperature and due to the mean annual precipitation. It was shown for the first time that both trends are mutually determined: the intensity of biomass trend in relation to the temperature is changing when depending on the level of precipitation, and the intensity of biomass trend in relation to precipitation level is changing during to a transition from the cold zone to the warm one and vice versa.